2014
DOI: 10.1039/c4cp03484h
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency inverted polymer solar cells controlled by the thickness of polyethylenimine ethoxylated (PEIE) interfacial layers

Abstract: In this work, we investigate the effect of the thickness of the polyethylenimine ethoxylated (PEIE) interface layer on the performance of two types of polymer solar cells based on inverted poly(3-hexylthiophene) (P3HT):phenyl C61-butryric acid methyl ester (PCBM) and thieno[3,4-b]thiophene/benzodithiophene (PTB7):[6,6]-phenyl C71-butyric acid methyl ester (PC71BM). Maximum power conversion efficiencies of 4.18% and 7.40% were achieved at a 5.02 nm thick PEIE interface layer, for the above-mentioned solar cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 33 publications
0
30
1
Order By: Relevance
“…The low dark current values confirm a full PEIE surface coverage on ITO. At higher concentrations, we still observe low dark current values but the thicker PEIE layer increases the contact resistance that prevents photo-generated charge extraction32. In contrast, for lower concentrations our results show that despite low values of WF, higher dark current densities are observed.…”
Section: Resultscontrasting
confidence: 52%
“…The low dark current values confirm a full PEIE surface coverage on ITO. At higher concentrations, we still observe low dark current values but the thicker PEIE layer increases the contact resistance that prevents photo-generated charge extraction32. In contrast, for lower concentrations our results show that despite low values of WF, higher dark current densities are observed.…”
Section: Resultscontrasting
confidence: 52%
“…Here, the thickness of the PEIE layer is varied in order to control the shunt resistance and optimize the organic solar cells for indoor light. Previous studies [40], [41] have shown that PEIE is an insulator which can modify the series resistance and the work function of the cathode as a function of its thickness. PEIE thickness has also been shown to influence the reverse bias saturation dark current in organic photodiodes.…”
Section: Optimization Of Solar Cells For Indoor Lightmentioning
confidence: 99%
“…The series resistance value of the thin PEIE cell is close to that of a device with no PEIE (direct contact between the active layer and aluminum). Therefore, it can likely be attributed to a less than optimal charge extraction due to too thin of a layer [41]. On the other hand, the thick PEIE cell has a slightly higher series resistance than the medium PEIE cell, suggesting that the insulating nature of the PEIE starts to be impactful.…”
Section: Optimization Of Solar Cells For Indoor Lightmentioning
confidence: 99%
“…Polyethylenimine ethoxylated (PEIE) has been widely used as interface modified layer in in organic light emitting diodes and organic solar cells [32][33][34][35][36][37][38][39]. Zhou et al [34] has used PEIE to reduce the work function of metals as well as oxide electrodes.…”
Section: Introductionmentioning
confidence: 99%